Sterol-Dependent Induction of Plant Defense Responses by a Microbe-Associated Molecular Pattern from Trichoderma viride. Issue 2 (18th December 2013) - Sharfman, Miya; Bar, Maya; Schuster, Silvia; Leibman, Meirav; Avni, Adi
Abstract : Modulating the synthesis of sterols affects the ability of a fungal protein to induce plant innate immunity . Abstract: Plant-microbe interactions involve numerous regulatory systems essential for plant defense against pathogens. An ethylene-inducing xylanase (Eix) of Trichoderma viride is a potent elicitor of plant defense responses in specific cultivars of tobacco ( Nicotiana tabacum ) and tomato ( Solanum lycopersicum ). We demonstrate that tomato cyclopropyl isomerase (SlCPI), an enzyme involved in sterol biosynthesis, interacts with the LeEix2 receptor. Moreover, we examined the role of SlCPI in signaling during the LeEix/Eix defense response. We found that SlCPI is an important factor in the regulation of the induction of defense responses such as the hypersensitive response, ethylene biosynthesis, and the induction of pathogenesis-related protein expression in the case of LeEix/Eix. Our results also suggest that changes in the sterol composition reduce LeEix internalization, thereby attenuating the induction of plant defense responses.